2010
DOI: 10.1086/652996
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Evidence against the Mutualistic Nature of Hereditary Symbioses: A Comment on Faeth

Abstract: Associations between fungal endophytes and grasses have served as particularly useful systems for exploring the nature and significance of hereditary symbiosis. Here, we propose alternative explanations for recent work by Faeth, in which endophytes were proposed to function as reproductive parasites. Faeth argued that his data demonstrated a symbiosis-induced shift to earlier host reproduction that could generate parasitism through life-history trade-offs with growth/survival. We contend that identifying a sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 27 publications
1
36
0
Order By: Relevance
“…Since Neotyphodium endophytes have lost the capacity for sexual reproduction, their long-term persistence depends entirely on the host's fitness (Clay and Schardl 2002;Saikkonen et al 2004). These hereditary symbioses have generally been regarded as mutualisms (Clay and Schardl 2002;Rudgers et al 2010), although benefits to the host are frequently indirect and are not always clear (Mü ller and Krauss 2005;Cheplick and Faeth 2009). The net outcome for the plant can be understood as the sum of positive and negative endophyte effects, the balance of which is contingent on prevailing conditions (Saikkonen et al 1998;Saona et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Since Neotyphodium endophytes have lost the capacity for sexual reproduction, their long-term persistence depends entirely on the host's fitness (Clay and Schardl 2002;Saikkonen et al 2004). These hereditary symbioses have generally been regarded as mutualisms (Clay and Schardl 2002;Rudgers et al 2010), although benefits to the host are frequently indirect and are not always clear (Mü ller and Krauss 2005;Cheplick and Faeth 2009). The net outcome for the plant can be understood as the sum of positive and negative endophyte effects, the balance of which is contingent on prevailing conditions (Saikkonen et al 1998;Saona et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…As their fitness is directly tied to the fitness of their hosts, symbionts can increase in frequency within populations by conferring net benefits to host individuals, such as protection from natural enemies (Sachs et al 2004;Gundel et al 2008;Rudgers et al 2010). In accordance with previous experimental results for other host grass species (reviewed by Clay 1996; Cheplick and Faeth 2009), we found that endophyte presence strongly reduced the density of aphids attacking the native grass Poa autumnalis.…”
Section: Discussionmentioning
confidence: 99%
“…As in other positive species interactions (Bronstein 1994), the benefits conferred by protective symbionts may be conditional on several factors, including the abundance and identity of the host's natural enemies (e.g., Clay et al 2005;Afkhami and Rudgers 2009) as well as resource availability and the abiotic environment (reviewed by Cheplick and Faeth 2009). Protection interactions are perhaps more likely to be context-dependent than symbioses providing direct (e.g., nutritional) rewards because the presence/ abundance of a third species (the host enemy) is required for benefits to accrue, thus forming an indirect species interaction (Bronstein 1998;Rudgers et al 2010). However, relatively few studies have investigated factors affecting the strength of benefits conferred by most types of protection symbioses, with the exception of ant-plant interactions (reviewed by Bronstein 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Endophytes of native grasses can negatively affect host performance by reducing competitive ability (Faeth et al 2004), growth and reproduction (Faeth and Sullivan 2003). Specifically, they can alter host resource allocation to increase their own transmission, which sometimes reduces allocation to plant reproduction (Faeth 2009;Gorischek et al 2013;but see Faeth 2010;Rudgers et al 2010). Conversely, the positive effects of endophytes range from increased competitive ability (Vázquez-de-Aldana et al 2012) and allelopathy (Vázquez-de-Aldana et al 2011) to decreased preference and performance of herbivores on infected grasses (Crawford et al 2010).…”
Section: Introductionmentioning
confidence: 99%